Electromagnetic Waves Can Help Improve the Rate of Increase of Milk Feeds Per Day in Premature Infants With Necrotizing Enterocolitis: A Pilot Trial - Liu, Xuexiu; Zhang, Xianhong; Li, Luquan; Wang, Jianhui; Wu, Liping (Frontiers in Pediatrics, 2022)
Abstract Objective: To evaluate the effects of electromagnetic waves generated by a commercialized medical electromagnetic apparatus (trade name, TDP ,the Chinese phonetic abbreviation of "Te-ding Dian-ci-bo Pu")，which is used as an adjuvant to improve the increased volume of milk per day for the premature infant with necrotizing enterocolitis (NEC). Methods:This study was a prospective randomized clinical trial. A total of 103 premature infant patients were diagnosed with NEC II, but no need for surgery. The infants were randomly divided into the experience group and the control group by a randomized method using SPSS 24.0. Patients in the experience group were treated with TDP irradiation and routine interventions; those in the control group were treated with routine interventions. The increased volume of milk per day, the time of achieving total gastrointestinal nutrition , the velocity of weight gain,complication incidence rate were recorded and compared. Results: The increased volume of milk per day in the experience group were significantly greater than control group ( 2.69 (1.92~4.17) vs 1.57 (0.81~3.0), P =0.000). Compared to the control group, the time of achieving total gastrointestinal nutrition (21.45 ± 1.87 vs 36.43 ± 2.585, P = 0.000),the velocity of weight gain(19.65 ± 15.27 vs 13.68 ± 7.15, P = 0.013) in the experience group were substantially better than those in the control group. Complications incidence rate:there was no significant difference between the two group (P > 0.05). Conclusion: TDP-generated electromagnetic waves were effective for the treatment of improving the volume of milk per day of premature infant patients with NEC Ⅱ, conducive to improving their clinical outcomes.